A study in Charlotte : a Charlotte Holmes novel - Cavallaro, Brittany (Cavallaro, Brittany. Charlotte Holmes novel., 2016)
Sherlock Holmes and Dr. Watson descendants, Charlotte and Jamie, students at a Connecticut boarding school, team up to solve a murder mystery.